Patriarchy and marital disharmony amongst Nigerian Christians: Ephesians 5:22–33 as a response - Ademiluka, Solomon O. (HTS teologiese studies, 2021)
This article employs the descriptive and exegetical methods. It found several ways by which patriarchy precipitates marital disharmony in Nigeria. For instance, the custom of the bride price instils in the husband the feeling of ownership of the wife, which encourages some men to treat their wives like their property. The nature of marital disharmony varies with couples, but there are some common characteristics. The husband may withdraw from his wife, avoiding all forms of contact and communication with her; wife beating is also common. Ephesians 5:22-33 mitigates the patriarchal view of marriage, redefining the concepts of submission and leadership. The wife should submit to her husband’s authority as she would to Christ whilst the husband should exercise his authority with love in imitation of Christ. When this new definition of marital relationship is understood and applied by Christian couples, disharmony will be considerably alleviated. The church should be involved in the application of the text, teaching husbands particularly the need to exercise their authority in sacrificial love.Contribution: The article endorses the journal’s focus on the combination of the notions ‘source’ and ‘interpretation’ by its emphasis on the exegesis of writings in the field of early Christian literature.